Self-repelling fractional Brownian motion : a generalized Edwards model for chain polymers - Bornales, Jinky (2015)
We present an extension of the Edwards model for conformations of individual chain molecules in solvents in terms of fractional Brownian motion, and discuss the excluded volume effect on the end-to-end length of such trajectories or molecules.